Discrete Element Analysis of the Load Transfer Mechanism of Geogrid-Ballast Interface under Pull-Out Load - Jing Li; Ya-Fei Jia; Chen-Xi Miao; Ming-Xing Xie (Advances in Civil Engineering)
Geogrids have been extensively used in subgrade construction for stabilization purposes of unconfined ballast. Based on well-calibrated microparameters, a series of geogrid-reinforced ballast models with different geogrid sizes and particular structures were developed to reproduce the mechanical behavior of the geogrid under pull-out load in this paper. And the rationality of the DEM model is verified by comparing the evolution law pull-out force measured by laboratory tests and numerical simulations under comparable conditions. Moreover, the macro pull-out force and the internal force distribution of the geogrid were analyzed, and the contact force statistical zones of the particle system were divided accurately according to the results. Meanwhile, both the force transfer mechanism in the geogrid-ballast interface and the sectionalized strain of the geogrid were discussed. And results unveil that the pull-out load is transmitted along the longitudinal ribs to the transverse ribs, and nearly 90% of the load is transmitted to the contact network (in statistical zone 1) in front of the first transverse rib, resulting in strong interlocking between the particles occurs in statistical zone 1. And the second transverse rib is the strength dividing line between strong and weak contact forces. Then, additional pull-out tests on the control groups were conducted, and the sectionalized strain of the geogrid and the peak pull-out force, as well as the energy dissipation were systematically analyzed. In addition, the proposed method used in simulation holds much promise for better understanding of the reinforcement mechanism and further optimizing the performance of geogrid-reinforced structures.